Reclaiming Our Original Identity: Communion, Community and Ministry - Díaz, Luz Marina (The way, 2024)
The article focuses on the profound significance of baptism and the exploration of one's identity as beloved children of God, drawing from the narrative of Jesus' baptism and insights from Henri Nouwen. Topics include the spiritual task of acknowledging this original identity, the temptations to deviate from it, and the timeless importance of communion, community, and ministry in cultivating and maintaining a loving relationship with God.